2019
DOI: 10.1029/2019ja026698
|View full text |Cite
|
Sign up to set email alerts
|

SAPS in the 17 March 2013 Storm Event: Initial Results From the Coupled Magnetosphere‐Ionosphere‐Thermosphere Model

Abstract: Subauroral polarization stream (SAPS) is latitudinally narrow flow channels of large westward plasma drifts in the subauroral ionosphere. In this study, the global structure and dynamic evolution of SAPS are investigated by using the Coupled Magnetosphere‐Ionosphere‐Thermosphere model with ring current extension, namely, the Lyon‐Fedder‐Mobarry‐Thermosphere Ionosphere Electrodynamics General Circulation Model‐Rice Convection Model, to simulate the 2013 St. Patrick's Day storm event. This is the first time that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 54 publications
(83 reference statements)
4
45
0
Order By: Relevance
“…It can be seen that both SAPS flow and ion vertical flow are much stronger when the IMF clock angle is between −180° and −90° (i.e., negative By and negative Bz ). For IMF Bz dependence, other studies indicate that SAPS will move equatorward with a larger magnitude when IMF Bz becomes stronger southward, a condition often associated with enhanced geomagnetic activity and extended convection pattern (Horvath & Lovell, 2016; Lin et al, 2019). For IMF By dependence, it is known that the main effect of By is to change the shape and orientation of the two‐cell convection pattern, in particular when Bz is negative (Heelis, 1984; Heppner & Maynard, 1987; Weimer, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that both SAPS flow and ion vertical flow are much stronger when the IMF clock angle is between −180° and −90° (i.e., negative By and negative Bz ). For IMF Bz dependence, other studies indicate that SAPS will move equatorward with a larger magnitude when IMF Bz becomes stronger southward, a condition often associated with enhanced geomagnetic activity and extended convection pattern (Horvath & Lovell, 2016; Lin et al, 2019). For IMF By dependence, it is known that the main effect of By is to change the shape and orientation of the two‐cell convection pattern, in particular when Bz is negative (Heelis, 1984; Heppner & Maynard, 1987; Weimer, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…However, their study employed an empirical neutral wind model and therefore did not include the feedback effect between neutrals and ions. Other recent progresses in the area of SAPS research involve fully coupled magnetosphere‐ionosphere‐thermosphere models, with a primary focus on the magnetosphere‐ionosphere coupling processes that produce the SAPS structures during the March 2013 storm (e.g., Lin et al, ; Raeder et al, ). These efforts represent an important advance in understanding the formation of SAPS and its impact on the magnetosphere‐ionosphere‐thermosphere system.…”
Section: Discussionmentioning
confidence: 99%
“…As we mentioned above, we only focused on the influences of SAPS electric field on the E × B drift of the flux tube and on the field‐aligned cold plasma transport from SED region to the plasmaspheric plume. However, SAPS have been considered to have much more profound effects on magnetosphere‐ionosphere‐thermosphere coupling process (e.g., Lin et al, ; Wang et al, ; Yuan et al, ; Zou et al, ). Moreover, many studies have been conducted on ion flows and transport at high latitudes, which showed that multiple processes are involved (Tu et al, ; Wang et al, ; Yuan et al, ; Zeng & Horwitz, ).…”
Section: Discussionmentioning
confidence: 99%